Environmental distribution and genomic characteristics of Solirubrobacter, with proposal of two novel species - Jiang, Zhu-Ming; Mou, Tong; Sun, Ye; Su, Jing; Yu, Li-Yan; Zhang, Yu-Qin (Frontiers in Microbiology, 2023)
Solirubrobacter spp. are abundant in soil samples collected from deserts and other areas with high UV radiation. In addition, a novel Solirubrobacter species, with strain CPCC 204708T as the type, was isolated and identified from sandy soil sample collected from the Badain Jaran Desert of the Inner Mongolia autonomous region. Strain CPCC 204708T was Gram-stain positive, rod-shaped, non-motile, non-spore-forming, and grew optimally at 28–30°C, pH 7.0–8.0, and in the absence of NaCl. Analysis of the 16S rRNA gene sequence of strain CPCC 204708T showed its identity within the genus Solirubrobacter, with highest nucleotide similarities (97.4%–98.2%) to other named Solirubrobacter species. Phylogenetic and genomic analyses indicated that the strain was most closely related to Solirubrobacter phytolaccae KCTC 29190T, while represented a distinct species, as confirmed from physiological properties and genomic comparisons. The name Solirubrobacter deserti sp. nov. was consequently proposed, with CPCC 204708T (= DSM 105495T = NBRC 112942T) as the type strain. Genomic analyses of the Solirubrobacter spp. also suggested that Solirubrobacter sp. URHD0082 represents a novel species, for which the name Candidatus “Solirubrobacter pratensis” sp. nov. was proposed. Genomic analysis of CPCC 204708T revealed the presence of genes related to its adaptation to the harsh environments of deserts and may also harbor genes functional in plant-microbe interactions. Pan-genomic analysis of available Solirubrobacter spp. confirmed the presence of many of the above genes as core components of Solirubrobacter genomes and suggests they may possess beneficial potential for their associate plant and may be important resources for bioactive compounds.